KEBIJAKAN MONETER DAN FISKAL DALAM ISLAM - Siti Mujiatun (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
One of the Government's strategy is to promote the public welfare aspects of economic life. Economic development can be done with a variety of strategies. Among others, is to empower wealth of natural resources that have been created by God. The government can open a gold mine, silver, coal, kerosene, gas, tin, etc. stored in the bowels of the earth as a natural form of empowerment. From other dimensions, to maximize the ability of the economy, the government can make monetary and fiscal policy. In this paper, the authors will describe how government policy in the monetary and fiscal aspects of economic empowerment.Broadly speaking, the Islamic version of the fiscal policy differs from fiscal policy non-Islamic version. Although there are similarities definitions and common purpose, but there are substantial differences from the legal basis used, method (either way gathering up the distribution) is in use, state income instruments used by the system. Foundation has always been a foothold in the Islamic system of fiscal policy is the Al Qur’an. Fiscal policy that was built by the Rasulullah saw is the first economic system must have a strong ideology based on religion.Method of distribution was at the time the leadership of the Rasulullah saw and Khulafaurrasidin the right target and direct manner without any hidden treasures. Distinguish between the wealth of the country is essentially a property right of the people to the authorities. Directions distribution on target with reference to the Al Qur'an (9: 60) is entitled to receive zakat or the wealth of the country is eight asnab. No human criteria used at that time. In terms of state income instruments there are significant differences.Islam does not justify the practice to provide tolerance to interest on loans. To maintain economic stability, Islam does not justify the government to practice usury in foreign loans. In contrast to Indonesia, where the system of interest in foreign loans is becoming gods, so that Indonesia became the country that depend continuously. So as we see, for the long time we are in crisis due to wrong economic system.